2013
DOI: 10.3329/jsr.v5i2.13213
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Anti-microbial Activity Studies on <i>Leea macrophylla</i> Seed Extracts

Abstract: Seed extracts of medicinal plants Leea macrophylla were investigated for phytochemical as well as antibacterial screening. Phytochemical studies of the plant extracts revealed the presence of phenolic, saponin, glycosides, carbohydrate and protein types of compounds. The antibacterial effects of the plant extracts were also tested against several human multidrug resistant pathogens, including one gram positive and three gram negative bacterial species and one fungal species using the disc-diffusion assay. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…In Bangladesh, the plant is found in Chittagong, Rajshahi, Natore and other northern parts of the country [7]. The plant has been observed useful in cancer [8], arthritis, goiter and tetanus [9], urolithiasis [10], hepatic damage [11] and microbial infection [12]. This research investigated whether antioxidative effects of LM contribute as neuroprotective as well as antiamnesic in diazepaminduced animal model.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, the plant is found in Chittagong, Rajshahi, Natore and other northern parts of the country [7]. The plant has been observed useful in cancer [8], arthritis, goiter and tetanus [9], urolithiasis [10], hepatic damage [11] and microbial infection [12]. This research investigated whether antioxidative effects of LM contribute as neuroprotective as well as antiamnesic in diazepaminduced animal model.…”
Section: Introductionmentioning
confidence: 99%
“…[46] Ethyl acetate extract of seed was more effective against Staphylococcus aureus compared to n-hexane, chloroform, and methanol extracts. [47] Joshi et al recently reported that root tuber ethanolic extract is highly effective against S. aureus, Staphylococcus flexneri, and Staphylococcus boydii, whereas less effective against Staphylococcus typhi and Klebsiella pneumoniae. MIC depicted values ranging from 0.195 mg/mL to 3.125 mg/mL.…”
Section: Economical Usesmentioning
confidence: 99%
“…They play a fundamental role in the proliferation and production of the plants besides performing as protecting system mechanisms against pathogens, parasites,and predators [60]. Simple phenols and phenolic acids are precursor to the synthesis of other complex compounds such as Flavonoids and tannins [61]. They act in the natural defense effective of plants to prevent them from infectious diseases and reduce the growth of pathogenic bacteria, viruses, and fungi.…”
Section: Phenolicsmentioning
confidence: 99%